Case report: Orthostatic leg tremor as the initial manifestation in a patient with metabotropic glutamate receptor-5 encephalitis without cortical dysfunction: complexities in identification and treatment - Yang, Xia; Liu, Qiong; Lai, Ming-feng; Ma, Xiao-hong; Hao, Xiao-ting; Xu, Jia-jun; Guo, Wan-jun (Frontiers in Neurology, 2023)
Objective: Metabotropic glutamate receptor 5 (mGluR5) encephalitis is such a rare type in autoimmune encephalitis that its' diagnosing remains a challenge.Case report: A 19-year-old female patient who initially presented anxiety and orthostatic leg tremor without cortical dysfunction. We found that mGluR5 antibodies of this patient were positive both in serum (1:1000) and in cerebrospinal fluid (1:32). After comprehensive intervention, the patient completely recovered at 18 months follow-up survey.Discussion: This report expands our knowledge of the possible presentations of mGluR5 encephalitis for early diagnosis, which makes it possible to prevent serious consequences and improve the prognosis.